2015
DOI: 10.1159/000375324
|View full text |Cite
|
Sign up to set email alerts
|

Cost Analysis of Early versus Delayed Loop Ileostomy Closure: A Case-Matched Study

Abstract: Background/Aims: The optimal timing for the closure of loop ileostomies remains controversial. The aim of the current study was to investigate whether early ileostomy closure (EC) (<2 weeks post-formation) results in significant healthcare savings as against late closure (LC). Methods: Patients with available cost data that underwent EC between January 2008 and December 2012 were compared against matched patients undergoing LC during the same period. Direct hospital costs for the two groups were compared. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 36 publications
1
25
0
1
Order By: Relevance
“…Early closure of a temporary stoma has been associated with significantly fewer postoperative complications up to 12 months after rectal resection in a randomized controlled trial [13]. Although the routine use of a temporary stoma in patients operated with low anterior resection increases the hospital costs of surgical treatment for rectal cancer [12], early closure of such may be a cost-effective alternative [14].…”
mentioning
confidence: 99%
“…Early closure of a temporary stoma has been associated with significantly fewer postoperative complications up to 12 months after rectal resection in a randomized controlled trial [13]. Although the routine use of a temporary stoma in patients operated with low anterior resection increases the hospital costs of surgical treatment for rectal cancer [12], early closure of such may be a cost-effective alternative [14].…”
mentioning
confidence: 99%
“…Third, this meta-analysis did not address cost efficacy. The cost savings associated with early versus late ileostomy reversal was reported in a case-matched study involving 103 patients [40]. Direct hospital costs were compared and it was found that early closure reduced healthcare costs by approximately 25%, despite higher wound infection rates [40].…”
Section: Discussionmentioning
confidence: 99%
“…The cost savings associated with early versus late ileostomy reversal was reported in a case-matched study involving 103 patients [40]. Direct hospital costs were compared and it was found that early closure reduced healthcare costs by approximately 25%, despite higher wound infection rates [40]. The overall reduced hospital stay combined with savings in stoma care may make this a cost-effective approach, but further study is needed to clarify this.…”
Section: Discussionmentioning
confidence: 99%
“…Однако, как указали авторы, выгоды от столь быстрой выписки могут нивелироваться увеличением стоимости за счет увеличения частоты повторных госпитализаций, достигающей 10,7%. Закрытие илеостомы менее, чем через 2 недели после ее формирования, также позволяет сокращать расходы (13724 против 16728 €, р=0,01), однако уровень осложнений достоверно увеличивается [11,24]. К сожалению, в настоящее время нельзя экстрапо-лировать результаты, полученные американским и европейским сообществом хирургов, на территорию Российской Федерации, так как различие экономических систем, производства, школ хирургов, социальных условий проживания пациентов -безусловно, накладывают свой отпечаток на качество и уровень хирургии в нашей стране.…”
Section: экономическая эффективность ликвидации двуствольных илеостомunclassified